Utility of the Personality Assessment Inventory for Detecting Malingered ADHD in College Students. (September 2016) - Musso, Mandi W.; Hill, Benjamin D.; Barker, Alyse A.; Pella, Russell D.; Gouvier, Wm. Drew
Objective: The purpose of the current study is to examine the utility of the Personality Assessment Inventory (PAI) for detecting feigned ADHD in college students.Method: A sample of 238 undergraduate students was recruited and asked to simulate ADHD (ADHD simulators) or respond honestly (controls) on the PAI. Archival data ( n = 541) from individuals diagnosed with clinical ADHD, no diagnosis, learning disorder, mood/anxiety, comorbid ADHD-mood/anxiety, or suspect effort were used.Results: Few individuals scored above the cutoffs on PAI validity scales. When alternative cutoff scores were examined, cutoffs of ≥77 on the Negative Impression Management (NIM) scale, ≥3 on the Malingering Index (MAL), and ≥1 on the Rogers Discriminant Function (RDF) yielded excellent specificity in all groups and sensitivities of .33, .30, and .20, respectively.Conclusion: Individuals who were asked to simulate ADHD easily manipulate the PAI; however, alternative cutoff scores proposed for PAI validity indices may improve the detection of feigned ADHD symptoms.